2021
DOI: 10.2174/1570159x18666200729092332
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Strategy for Congenital Myasthenic Syndrome with CHRNE Mutations: A Meta-Analysis of Case Reports

Abstract: Background: Congenital myasthenic syndromes (CMSs) are a heterogeneous group of neuromuscular disorders. Mutations of the nicotinic acetylcholine receptor epsilon subunit gene (CHRNE) are the most common causes of these disorders. CMSs are gaining increasing recognition by clinicians. However, pharmacological treatment of CMS with CHRNE mutations has only been discussed in a small number of case reports. Objective: This study aims to determine how to choose an appropriate pharmacological strategy for CMS wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The search strategy used was modified from previous study ( 16 ). The literature search was restricted to articles published in English.…”
Section: Methodsmentioning
confidence: 99%
“…The search strategy used was modified from previous study ( 16 ). The literature search was restricted to articles published in English.…”
Section: Methodsmentioning
confidence: 99%
“…28 Recently, NGS has become more widely available, leading to an increasing understanding not only of GNE myopathy-related mutations, but also of other myopathies. 29 At present, there is no effective therapy available for GNE myopathy. 30,31 Preclinical studies have identified that the use of oral monosaccharides reversed muscle hyposialylation in a GNE myopathy mouse model.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Recently, NGS has become more widely available, leading to an increasing understanding not only of GNE myopathy‐related mutations, but also of other myopathies. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The Pearson chi-square (χ 2 ) test was used to compare the frequency distribution of categorical variables. The Mann-Whitney U test or Kruskal-Wallis test was used to compare the difference among different groups as previously used 13 . The statistical analysis was performed using the Statistical Package for Social Sciences (SPSS Inc., Chicago, IL, USA) Version 20.…”
Section: Methodsmentioning
confidence: 99%